Pengayaan sumber belajar sejarah berbasis situs cagar budaya ragawi di Kabupaten Sidoarjo - Reza Hudiyanto; Ismail Lutfi; Ronal Ridhoi (Universitas Negeri Malang, 2026)
Enrichment of history learning resources based on the ragawi cultural heritage site in Sidoarjo Regency Sidoarjo Regency possesses a wealth of tangible cultural heritage sites ranging from the Classical to the Colonial era, offering significant potential as history learning resources. However, this potential has not been optimally utilized in school learning due to the lack of valid teaching materials and limited accessibility of academic references for teachers. This community service activity aims to enhance teachers' competence in utilizing lokal sites as learning media through the development of research-based teaching materials. The implementation method employs a participatory approach with the Musyawarah Guru Mata Pelajaran (MGMP) of Senior High Schools (SMA/SMK/MA) in Sidoarjo Regency as the partner. The activity series includes Focus Group Discussions (FGD) for needs analysis, workshops on archaeological knowledge transfer, and intensive mentoring for book manuscript drafting. The results show an increased understanding among teachers regarding the historiography and archaeological data of Candi Pari, Candi Sumur, and colonial industrial buildings. The main output of this program is the compilation of a draft titled